Prayer as a dialogue between person and God: the religious aspect - Предко, О. (Київський національний університет імені Тараса Шевченка, 2019)
The author notes that prayer is a kind of mental state, which is characterized by extreme intensification of the emotional sphere, which ultimately leads to the transformation of a person, breakthrough into the sphere of the Divine. Moreover, the procedural nature of the prayer highlights the spiritual horizons of the being of a person, allows expanding its spiritual and transcendental meanings of existence. This would certainly contribute to the substantiation of the type of philosophizing that would combine the rational and the irrational and thereby serve both the mind, feeling and morality in the personality formation, its involvement in the sphere of the Divine. Prayer acts as a catalyst for the activity of the consciousness of the subject, his spirituality. It provides a person support for his target attitude, relieving internal stresses. Priority is its role in extreme situations when the maximum concentration of spiritual and physical forces of the person is required. Prayer practices act as a generator of energy, support the inner attitude of a person, necessary for further activities and for overcoming difficulties. In fact, the prayer becomes the generator of the formation of a kind of subjective reality of a person, sets its style of life and thinking. Prayer is the phenomenon by which not only certain meanings are found by person, but also indicators of the existence of a certain hierarchy of values and landmarks are verified. Spiritual prayer experience is the experience of human existence, the experience of "gathering oneself" from scattered parts, where a person is both an artist and a work of art, where not only one has to live, but also to comprehend, to create not only oneself in the process of this reflection, but also the world of the Other. Therefore, the prayer process forms the complex architectonics of the spiritual mode of being of a person, sets its viability, thanks to which it is self-determined, aiming at dialogue with the Absolute.

Зазначається, що молитва – це своєрідний психічний стан, який характеризується надзвичайною інтенсифікацією емоційно-чуттєвої сфери, що врешті-решт призводить до переображення людини, прориву її в царину Божественного. Причому процесуальний характер молитви висвічує духовні обрії буттєвості людини, дозволяє розширити її духовно-трансцендентні сенси існування, що, безперечно, сприятиме обґрунтуванню такого типу філософування, який би поєднував би раціональне та ірраціональне і тим самим служив би і розуму, і почуттю, і моральності у формуванні особистості, її причетності до сфери Божественного. Молитва виступає як каталізатор активності свідомості суб'єкта, його духовності. Вона забезпечує людині підтримку її цільової установки, зняття внутрішньої напруги. Пріоритетною є її роль в екстремальних ситуаціях, коли потрібна максимальна концентрація духовних і фізичних сил людини. Молитовні практики виступають генератором енергії, підтримують внутрішню установку людини, необхідну для подальшої діяльності і для подолання труднощів. Фактично, молитва стає генератором формування своєрідної суб'єктивної реальності людини, яка задає її стиль життя і мислення. Тому молитовний процес формує складну архітектоніку духовного способу буття людини, задає її життєздатність, завдяки чому вона самовизначається, націлюючись на діалогічне спілкування з Абсолютом.
Молитва як діалог людини та Бога: релігієзнавчий аспект
Keywords: prayer; dialogue; spirituality; request-response; person-God relations; молитва; діалог; духовність; запит-відгук; відношення людина-Бог